The Bam repeats of the mouse genome belong in several superfamilies the longest of which is over 9 kb in size. - Meunier-Rotival, M (1984)
Mouse DNA contains two equally abundant, homologous subfamilies of MspI 3.6 and 5 kb repeated fragments. The first subfamily corresponds to the previously described (1) Bam 4 kb repeats, the second one to Bam repeated fragments of higher molecular weight. These subfamilies account for the vast majority of long Bam repeats and are linked with contiguous short Bam 0.5 kb repeats. A minority of these composite Bam repeats extend, on the 0.5 kb side, into R repeats. In turn, a fraction of the composite Bam/R repeats extend further, for at least 3 kb, into other repeated sequences contiguous to the R repeats. The long Bam repeats belong, therefore, in at least three superfamilies of repeats, the longest one being over 9 kb in size. Some general properties of these superfamilies are discussed.